2020
DOI: 10.1111/andr.12891
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves sperm DNA quality and reproductive capacity in type 1 diabetes

Abstract: Background In the coming decades, diabetes mellitus might affect 628 million individuals. Its final impact on male fertility and reproductive outcomes should be considered since the number of adolescents and young adults presenting diabetes is rising. Resveratrol (RES), a polyphenol, is a biological modulator with multitarget and multi‐action characteristics. Objectives to evaluate if RES is effective against the male reproductive damage caused by type 1 diabetes (DM1), focusing on sperm DNA integrity and repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 96 publications
(208 reference statements)
0
26
0
Order By: Relevance
“…Another pathological situation that can induce lipid peroxidation and therefore increase oxidative stress and damage related to fertility is type 1 diabetes mellitus (DM1). RSV has been shown to be useful in improving the parameters of fertility altered by this pathology: lipid peroxidation, fragmentation of spermatic DNA, alteration of chromatin and mitochondrial mass [111].…”
Section: Resveratrolmentioning
confidence: 99%
“…Another pathological situation that can induce lipid peroxidation and therefore increase oxidative stress and damage related to fertility is type 1 diabetes mellitus (DM1). RSV has been shown to be useful in improving the parameters of fertility altered by this pathology: lipid peroxidation, fragmentation of spermatic DNA, alteration of chromatin and mitochondrial mass [111].…”
Section: Resveratrolmentioning
confidence: 99%
“…We and others have shown that diabetes is associated with testicular damage in murine models [ 42 , 73 , 74 ]. As expected, treatments that lower hyperglycemia can restore spermatogenesis and steroidogenesis in diabetic animals (increased sperm count, sperm motility, and testosterone) [ 73 , 75 , 76 ]. In addition, administration of metformin, the first-line treatment for type-2 diabetes in men with diabetic complications, improves sperm concentration and sperm chromatin integrity [ 77 ].…”
Section: Covid-19-associated Diabetes Reduces Male Fertilitymentioning
confidence: 52%
“…In addition to the various mechanisms related to reduced fertility in our article, it is also possible that other mechanisms may lead the damaged fertility. It has demonstrated widely that decreased sirt1 causes mitochondrial dysfunction by increasing oxidative stress levels and apoptosis in male sperms, leading to infertility ( 55 , 56 ). In addition, when it has demonstrated that seminal sirt1 expression was significantly lower in infertile men than fertile men, a recent study demonstrated that sirt1 can regulate acrosome biogenesis by modulating autophagic flux during spermiogenesis in mice ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%